Quizizz-Based Science Learning Evaluation as an Effort to Improve Learning Outcomes of Fourth Grade Students at SDN Inpres Campa - Asmaul Hikmatan; Antika Antika (Prodi PGMI STIT Sunan Giri Bima, 2026)
This research is motivated by the importance of strengthening character education through Pancasila and Citizenship Education (PPKn) learning in elementary schools, especially in instilling Pancasila values contextually. The purpose of this study is to analyze the effectiveness of the project-based learning model in improving the understanding and internalization of Pancasila values in fourth grade students. This study uses a quantitative approach with a quasi-experimental design. The subjects of the study were fourth grade students who were divided into an experimental class and a control class. Data collection techniques used learning outcome tests and observation sheets, while data analysis was carried out through statistical tests to determine differences in learning outcomes between the two groups. The results showed that there was a significant increase in students' understanding and attitudes towards Pancasila values in the experimental class compared to the control class. These findings indicate that the project-based learning model is effective in supporting more meaningful and contextual PPKn learning. Thus, the application of this model is recommended as an alternative learning strategy to strengthen character education in elementary schools.